emozioni, empatia e realtà virtuale: alcune riflessioni a partire da Julie VR (Materiali di Estetica. Terza serie, 2025)
This article aims to offer some reflections on the nature of emotions generated by virtual reality (VR). We seek to explore the capacity of this kind of immersive digital experience to elicit empathy in the user. However, we are not dealing with just any VR experience: our reflections stem from a concrete case of virtual reality theatre production—Julie VR. The article thus aligns with the field of research that analyzes immersive digital experiences as “empathy machines”. After presenting the Julie VR experiment, which was developed within the CHANGES project funded by the PNRR in 2024, we introduce the concepts of presence and immersivity in VR theatrical environments, outlining their complex relationship with the emotions generated by the drama Julie. In the third section, we delve into the nature of the emotions experienced by the VR viewer, relating them on one hand to the issue of narrativity, and on the other to the role of the projected body within the image space of VR. Finally, we sharpen our analysis of emotions and VR by focusing on empathy, understood as the emotion that most clearly highlights the potential of VR experiences to generate emotional engagement and foster empathic connection.
Keywords: emotion; virtual reality; empathic machine; immersivity